The event of death: Reflections on the dynamics of emotions and embodied resistance in the Moroccan Contexts of hirak (movement) and la hirak ((non)movement). Issue 4 (4th July 2019) - Moulay Driss, El Maarouf; Belghazi, Taieb
ABSTRACT: This paper studies the role of emotions in creating spectacular revolt situations. We underline the travelling competence of sentiments and their power in crafting trans-local moments of embodied resistance. In contemporary Moroccan society, the adaptation of the Bouazizian style of protest has been a reaction to the prevailing feelings of worthlessness gripping the common citizen. The images of wasted beings in the post-2011 atmosphere have been associated with instances of social insurgence, by individuals who attempt self-immolation, or citizens treated by figures from the centre (e.g. police, public figures) in a way that inculcate in them powerful feelings of abjection, after which they feel irreparably delinked from their sense of humanity. This paper seeks to demonstrate how practices of al-hogra (humiliation) have produced cultural forms of abjection that could also be traced in the way common people inferiorize one another in everyday life through the use of a terminology of trash. By disclosing people's non-subtle armaments of protest (i.e. self-immolation), we contend that resistance and its various trances, as well as the emotions that prompt them, have their origin in the reality of the body, realistic visions of the body owner and his/her awareness of the potential for realization (through it). Hence we will examine how vulnerable people manipulate the three conditions of corporeality, corporealism and corporealization, to subvert the humiliation and symptoms of social death imposed on them by the regime.